UNIVERSITY SAVINGS FUND - Salcedo Guzmán, Luisa Elena (2011)
This article seeks to capture the most relevant results were obtained in 2011, as part of development of the Research Project SIN-SIN, entitled, College Savings Fund. The project aimed to outline the model of common Savings Fund, an investment program student - university savings fund -in which the student through voluntary contributions to access to future credits redituen their academic projections. Today, a national study shows that only 35% of students graduating from a race superior and another percentage is even larger in the attempt to causes of unfavorable economic conditions. So what is sought for this project was to demonstrate that the College Savings Fund can not only promote the savings habit among students but can also be a mechanism to improve their standard of living or future.